The distribution of waterfowl to St. Lawrence Island, Alaska - Fay, Francis H (Wildfowl, 1961)
Twenty-two species of waterfowl are represented on St. Lawrence Island. Twelve of these breed on the island, and the rest occur irregularly or as migrants. The surrounding waters constitute a major wintering area for Long-tailed Ducks (Clangula hyemalis) and King Eiders (Somateria spectabilis), while in summer the island is an important breeding and moulting area for Emperor Geese (Anser canagicus), Pacific Eiders (Somateria mollissima v-nigra), Northern Pintails (Anas acuta acuta), and Long-tailed Ducks. Seasonal occurrence and some features of natural history of the more common species have been described. The avifauna of St. Lawrence Island is more closely affiliated with that of North America than Asia. This may be a result of the island's relationship to the Bering Land Bridge, which probably had a strong influence on the intercontinental distribution of waterfowl. With gradual inundation of the land bridge during the last part of the Wisconsin (Wrm) glacial epoch, the island's faunal tie to North America probably was weakened. A decrease in abundance of North American forms is indicated by a comparison of the Eskimo's waterfowl harvests of 1-2000 years ago with those of the present.